Bilateral Audiometric and Acoustic Analysis of High Frequency Fricatives in Students with Speech Impairments (2024)
"Some scholars assume that it is possible for people who have impaired perceptions to distort fricatives. Although this assumption has been investigated in other climes; it has attracted little or no attention in the Nigerian context. This study, therefore, investigates high frequency fricatives in students with speech impairments using bilateral audiometric and acoustic analysis with a view to determining whether speech impaired persons that cannot perceive high frequency can distort fricatives as widely assumed. The audiometry was used to test the average pure tone threshold of twelve students who gave their consents and six were purposively selected. The nature of data that was elicited contained lexical items with fricatives: Is, f, f, v, zI. It was called by the researcher for the subjects and they repeated it while their voices were recorded into Praat directly for spectrographic analysis. It was reported that speech impaired persons distorted the fricatives Is, f, f, v, zI in varying degrees. For instance, subjects A, B, and C, distorted the sound Isl as It!, in soap IS'Jup/, as top, !.Qmh..respectively. In the word sheep IflP 'I"", If I was distorted as It I and Itfl, as in: [ipu, chitem and choyon by the subjects, respectively. The findings support the claim that it is possible for people who have impaired perceptions and cannot perceive high frequencies to distort fricatives.